TYPES AND ACTIVITIES OF DAILY INSECT POLINATORS IN ORDER GARDEN AND GARDEN FRUIT LIWA - Devy Febriyanti; EMANTIS ROSA; Rochmah Agustrina (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
Pollinator insects are insects that play a role in pollinating plants. This research was conducted in December-January 2020 at the Liwa Botanical Garden which aims to determine the types and daily activities of pollinator insects in the Liwa Botanical Garden Ornamental and Fruit Parks. The research used observation methods in 2 locations, namely Ornamental Gardens and Fruit Gardens. Pollinator insect sampling using a sweap net. The data obtained were analyzed descriptively. The results found that including pollinator insects in the Ornamental Park were 11 species and 165 individuals, namely (Junonia orithya, Hypolimnas bolina bolina, Neptis clinioides gunongensis, Oriens gola, Euploea mulciber, Elymnias panthera, Apis cerana, Apis florea, Xilocopa confuse, Lucilia sericerata, Coccinella septempuncata), in the Fruit Garden there were 6 species and 276 individuals, namely (Bactrocera dorsalis, Eurema blanda, Zizina otis, Ypthima baldus newboldi, Apis cerana, and Apis florea). Observation of Junonia orithya's daily activities starts in the morning at 08: 00-11: 00 WIB. Flying activities are initiated by the butterfly around the flower plant then perching on the leaves to sunbathe, suck nectar, suck minerals, suck nectar repeatedly, and look for a partner to carry out mating activities. Observation of daily afternoon activities was carried out at 14: 00-16: 00 WIB Junonia orithya was seen carrying out her activities such as in the morning. When the brightness starts to decrease for example due to rain, the butterflies will rest and take shelter under the leaves or bush environment.